Flexible working arrangement scenario planning for the social security agency for employment - Ferryanto, Hanif; Maarif, Muhammad Syamsul; Taryana, Asep (Indonesian Journal of Multidisciplinary Science, 2025)
This study investigates the readiness of the Social Security Agency for Employment (BPJS Ketenagakerjaan) to implement flexible working arrangements (FWAs) in response to the evolving work landscape post-COVID-19. With the Indonesian government's reclassification of the pandemic, organizations are reconsidering their work models, making it crucial to assess their preparedness for hybrid work systems. The research employs a case study design with a descriptive approach, utilizing the TAIDA method to develop planning scenarios. Data collection includes primary data from in-depth interviews with experts and secondary data from relevant literature and internal documents. Findings reveal that BPJS Ketenagakerjaan demonstrates a very good level of readiness across various dimensions, including technology and management, with an overall readiness index of 82.58. However, the mobility policy dimension indicated potential improvement areas. The study highlights the importance of establishing clear policies and standard operating procedures to support remote work, particularly for employees with specific health needs. The implications of this research are significant for BPJS Ketenagakerjaan as it provides a structured framework for enhancing organizational readiness for FWAs, ensuring employee engagement and satisfaction. This study contributes to the broader discourse on flexible work arrangements, offering practical guidance for public service organizations navigating the complexities of hybrid work implementation.